2020
DOI: 10.3389/fpls.2020.00529
|View full text |Cite|
|
Sign up to set email alerts
|

Arabidopsis Plants Sense Non-self Peptides to Promote Resistance Against Plectosphaerella cucumerina

Abstract: Peptides are important regulators that participate in the modulation of almost every physiological event in plants, including defense. Recently, many of these peptides have been described as defense elicitors, termed phytocytokines, that are released upon pest or pathogen attack, triggering an amplification of plant defenses. However, little is known about peptides sensing and inducing resistance activities in heterologous plants. In the present study, exogenous peptides from solanaceous species, Systemins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 64 publications
(90 reference statements)
2
15
0
Order By: Relevance
“…The present results are also in agreement with other reports involving flagellin (Zipfel et al, 2004 ; Pastor-Fernández et al, 2020 ). In addition, and as expected, we have found that tomato plants sprayed with SA, JA, or ethylene increased expression of a wide range of defense-related genes, but 10 genes were unique to BP178 challenged plants.…”
Section: Discussionsupporting
confidence: 94%
“…The present results are also in agreement with other reports involving flagellin (Zipfel et al, 2004 ; Pastor-Fernández et al, 2020 ). In addition, and as expected, we have found that tomato plants sprayed with SA, JA, or ethylene increased expression of a wide range of defense-related genes, but 10 genes were unique to BP178 challenged plants.…”
Section: Discussionsupporting
confidence: 94%
“…The antifungal assay was carried out as already reported ( Pastor-Fernández et al, 2020 ; Molisso et al, 2021 ). A sterile 12-well plate was filled with potato dextrose broth (PDB 1/2) medium, containing ProSys fragments at the final concentration of 100 fM.…”
Section: Methodsmentioning
confidence: 99%
“…To assess if Sys had a direct antimicrobial effect on T. afroharzianum T22 , an in vitro assay was carried out to measure fungal growth in presence or absence of different concentrations of the peptide. Antifungal assays were conducted as previously described (Pastor-Fernández et al, 2020). Wells of a sterile 12-well plate were filled with 1 ml of half-strength potato dextrose broth (PDB 1/2) medium containing Sys, at a final concentration of 100 pM or 100 fM except for the negative control wells.…”
Section: Methodsmentioning
confidence: 99%
“…Antifungal assays were conducted as previously described (Pastor-Fernández et al, 2020). Wells of a sterile 12-well plate were filled with 1 ml of half-strength potato dextrose broth (PDB 1/2) medium containing Sys, at a final concentration of 100 pM or 100 fM except for the negative control wells.…”
Section: In Vitro Trichoderma-sys Compatibility Assaymentioning
confidence: 99%